2017
DOI: 10.4172/2167-0250.1000181
|View full text |Cite
|
Sign up to set email alerts
|

Extraversion and Neuroticism in Sexually Dysfunctional Men Suffering from Erectile Dysfunction and Premature Ejaculation: A Cross-Sectional Study

Abstract: The role of personality traits in sexual complaints and dysfunctions is ever more evident. However, the literature is very scarce as to the possible relationships between such personality traits and specific sexual dysfunctions like ED, PE or both, their subtypes as to time of onset and severity levels. The main aim of the present study was to investigate if Neuroticism and Extraversion have different roles and trends in men suffering from PE and/or ED, both lifelong and acquired. Moreover, we verified if, by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This current study opens up new angles to exploring gender relations in domestic violence cases in polygamous marriages in Uganda and fills a void in the research available. In Uganda, like in Turkey, a study by [33] revealed that Turkish women also scored higher in Neuroticism than other groups. Previous research [33] recommends that professionals working with female victims should help them ameliorate neuroticism to reduce risks of depressive symptoms.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This current study opens up new angles to exploring gender relations in domestic violence cases in polygamous marriages in Uganda and fills a void in the research available. In Uganda, like in Turkey, a study by [33] revealed that Turkish women also scored higher in Neuroticism than other groups. Previous research [33] recommends that professionals working with female victims should help them ameliorate neuroticism to reduce risks of depressive symptoms.…”
Section: Discussionmentioning
confidence: 98%
“…In Uganda, like in Turkey, a study by [33] revealed that Turkish women also scored higher in Neuroticism than other groups. Previous research [33] recommends that professionals working with female victims should help them ameliorate neuroticism to reduce risks of depressive symptoms.…”
Section: Discussionmentioning
confidence: 98%